Fiction: Simulation of Social Worlds. Issue 8 (August 2016) - Oatley, Keith
Abstract : Fiction is the simulation of selves in interaction. People who read it improve their understanding of others. This effect is especially marked with literary fiction, which also enables people to change themselves. These effects are due partly to the process of engagement in stories, which includes making inferences and becoming emotionally involved, and partly to the contents of fiction, which include complex characters and circumstances that we might not encounter in daily life. Fiction can be thought of as a form of consciousness of selves and others that can be passed from an author to a reader or spectator, and can be internalized to augment everyday cognition. Trends: In long-term associations and shorter-term experiments, engagement in fiction, especially literary fiction, has been found to prompt improvements in empathy and theory-of-mind. Improvements of empathy and theory-of-mind derive both from practice in processes such as inference and transportation that occur during literary reading, and from the content of fiction, which typically is about human characters and their interactions in the social world. Comprehension of stories shares areas of brain activation with the processing of understandings of other people. Both fiction and everyday consciousness are based on simulations of the social world; thus, reading a work of fiction can be thought of as taking in a piece of consciousness. The study of fiction helps us understand how imagination works to create possible worlds, and how mental models are formed of others and ourselves.